2021
DOI: 10.1016/j.omto.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophage-derived exosomal microRNA-155-5p promotes the immune escape of colon cancer by downregulating ZC3H12B

Abstract: Previous evidence has highlighted M2 macrophage regulation of cancer cells via exosome shuttling of microRNAs (miRNAs or miRs). The current study set out to explore the possible role of M2 macrophage-derived exosomal miR-155-5p in regard to immune escape of colon cancer cells. Experimental data from quantitative reverse-transcriptase PCR (qRT-PCR) and western blot analysis revealed highly expressed miR-155-5p and interleukin (IL)-6 and poorly expressed ZC3H12B in M2 macrophagederived exosomes. Additionally, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…Obesity-induced IL-6 expression promotes the polarization of M2 macrophages and induces secretion of the chemokine CC-chemokine ligand 20 (CCL20) in the CAC microenvironment; CCL20 recruits CC-chemokine receptor 6 (CCR6)-expressing B cells and γδ T cells via chemotaxis, leading to CAC progression [51]. It has been reported that exosomal miR-155-5p derived from M2 macrophages can accelerate the occurrence and development of colon cancer via its effect on ZC3H12B-mediated IL-6 stability [52]. Exosomal miR-1246, secreted by colon tumor spheres, increased the proportion of M2 polarized macrophages in vitro [53].…”
Section: Regulation Of Phenotypic Polarization Of Tams In Crcmentioning
confidence: 99%
“…Obesity-induced IL-6 expression promotes the polarization of M2 macrophages and induces secretion of the chemokine CC-chemokine ligand 20 (CCL20) in the CAC microenvironment; CCL20 recruits CC-chemokine receptor 6 (CCR6)-expressing B cells and γδ T cells via chemotaxis, leading to CAC progression [51]. It has been reported that exosomal miR-155-5p derived from M2 macrophages can accelerate the occurrence and development of colon cancer via its effect on ZC3H12B-mediated IL-6 stability [52]. Exosomal miR-1246, secreted by colon tumor spheres, increased the proportion of M2 polarized macrophages in vitro [53].…”
Section: Regulation Of Phenotypic Polarization Of Tams In Crcmentioning
confidence: 99%
“…Mechanically, AGAP2-AS1 negatively regulates miR-296, and NOTCH2 is targeted by miR-296. Thus, M2 macrophage-derived exosomal AGAP2-AS1 enhances radiotherapy immunity in lung cancer by reducing miR-296 and elevating NOTCH2 (Zhang F. et al, 2021).…”
Section: Radiotherapy Immunitymentioning
confidence: 98%
“…M2 macrophage-derived exosomal miR-155-5p promotes the development of colon cancer by inhibiting the expression of ZC3H12B in vivo . Delivery of miR-155-5p from M2 macrophage to colon cancer cells through exosomes impaires ZC3H12B-mediated IL-6 stability reduction, which consequently induced immune escape and tumor formation ( Ma et al, 2021 ).…”
Section: Tumor-associated Macrophages-derived Exosomes Influence Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, lung cancer cell-derived exosomes (from the A59 and H358 cell lines) alter the transcriptional and bioenergetic signature of M0 macrophages, leading them to an M2 phenotype [142]. However, the M2 macrophage-derived exosomes can transfer miR-21-5p and miR-155-5p to cancer cells, promoting the downregulation of transcription factor Brahma-related gene-1 (BRG1), leading to cell migration and invasion in colon cancer cells [141,143]. Gastric cancer showed similar results; M2 macrophage-derived exosomemediated apolipoprotein E (ApoE) transfer was found to increase the cancer cell migration in a PI3K/Akt signaling pathway activation-dependent manner [144].…”
Section: Cancer-derived Exosomes Regulate Tumor Promotion and Progressionmentioning
confidence: 99%